PERSEPSI SUSUNAN MENU KARYAWAN DI AP PREMIER HOTEL BATAM - Juniar, Reysha; Asnur, Lise (Journal of Food Technology and Agroindustry, 2024)
This research originated from the results of pre-research observations conducted by researchers by having short conversations with several employees at AP Premier Hotel Batam regarding the employee menu provided by the hotel. Based on the results of these conversations the researcher listened to some of the employee's comments regarding the menu served every day such as employees sometimes often being unable to eat, the food menu was cold, the fruit served was not fresh, the food menu served in the employee canteen was less varied, such as every weekend. This study aims to find out how employees evaluate employee menu settings at AP Premier Hotel Batam. Based on the research that has been done, the following results are obtained: (1) Employee menu arrangement variables in general can be categorized as not good with a percentage of 67.27% and 20% good enough. (2) The standard portion indicator is in the bad category with a percentage of 49.1% and 34.5% in the pretty good category. (3) In general, standard prescription indicators are in the bad category with a percentage of 54.5% and 30.9% in the pretty good category. (4) The standard seasoning indicator is classified as bad with a percentage of 54.5% and 30.9 in the fairly good category. (5) The quality standard indicators are categorized as bad with a percentage of 63.6% and 20% in the fairly good category. So that the arrangement of the employee menu at AP Premier Hotel Batam is categorized as not good, which requires improvement and requires attention from management.